1990
DOI: 10.1177/38.11.2212616
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of the two small proteoglycans biglycan and decorin in developing human skeletal and non-skeletal tissues.

Abstract: The messenger RNAs and core proteins of the two small chondroitin/dermatan sulfate proteoglycans, biglycan and decorin, were localized in developing human bone and other tissues by both 35S-labeled RNA probes and antibodies directed against synthetic peptides corresponding to nonhomologous regions of the two core proteins. Biglycan and decorin expression and localization were substantially divergent and sometimes mutually exclusive. In developing bones, spatially restricted patterns of gene expression and/or m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
355
2
19

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 617 publications
(393 citation statements)
references
References 14 publications
17
355
2
19
Order By: Relevance
“…The lower region of subepithelial mesenchyme might be matured and stabilized in the histological structure in view of the distribution of type I collagen and general histological findings [1]. It has been shown that decorin was distributed in the collagen rich region in the skin and skeletal muscles in human and bovine fetuses [2,13]. This was also the case in the present results as to the fetal bovine rumen.…”
Section: A)supporting
confidence: 75%
“…The lower region of subepithelial mesenchyme might be matured and stabilized in the histological structure in view of the distribution of type I collagen and general histological findings [1]. It has been shown that decorin was distributed in the collagen rich region in the skin and skeletal muscles in human and bovine fetuses [2,13]. This was also the case in the present results as to the fetal bovine rumen.…”
Section: A)supporting
confidence: 75%
“…Biglycan has been shown to be processed by BMP1/TLD-like proteinases in vitro and in vivo . Since biglycan is thought to play a positive role in bone formation (Bianco et al, 1990) and to be involved in regulating TGFβ signaling (Chen et al, 2002), its processing may represent novel mechanisms by which BMP1/TLD-like proteinases affect osteogenesis and TGFβ signaling (also see below), respectively. It should be cautioned however that it is not yet known how processing affects biglycan function.…”
Section: Non-collagenous Matrix Proteinsmentioning
confidence: 99%
“…Epiphyseal cartilage stains prominently for decorin and only weakly for biglycan, whereas in presumptive articular cartilage biglycan is found in the pericellular matrix whereas this developing zone is free of decorin. 30 In adult articular cartilage decorin is present in the interterritorial matrix while biglycan is found in the pericellular matrix. Decorin is associated with collagen fibrils as a decorating proteoglycan and carries one chondroitin or dermatan sulfate side chain.…”
Section: Other Than Aggrecanmentioning
confidence: 99%